Immunophenotyping of Thymic Lymphoma in a Nelore Cow - Sampaio, Paulo H.; Fidelis Junior , Otávio L.; Queiroz, Daniela J. de; Soares, Luciana M. C.; Moreira, Pamela R. R.; Vasconcelos, Rosemeri O.; Marques, Luiz C.; Alessi, Antonio C. (Brazilian Journal of Veterinary Pathology, 2012)
Thymic lymphoma is a malignant lymphoid neoplasm that affects several species, including cattle. This type of neoplasia can lead to death due to malignant cell infiltration in different organs. The classification of this neoplasm may predict prognosis and response to treatment. Immunophenotyping is one of the ways to perform this classification. There are reports about the performance of immunohistochemistry (IHC) to classify thymic lymphoma only in taurine cattle, therefore the aim of this report is to describe the immunophenotype of a thymic lymphoma in a Nelore cow. Immunostaining was performed with monoclonal antibodies (CD79, CD4 and CD8). The tumor cells showed positive staining only for CD8 T lymphocytes, coinciding with the disease progression, since the T lymphoma type is more aggressive.